Genotoxicity and cytotoxicity effects of X-rays on the oral mucosa epithelium at different fields of view: a cone beam computed tomography technique - Roghaieh Faeli Ghadikolaei; Hakimeh Ghorbani; Maryam Seyedmajidi; Kourosh Ebrahimnejad Gorji; Ehsan Moudi; Seyedali Seyedmajidi (Babol University of Medical Sciences, 2023)
Background: Cone beam computed tomography (CBCT) is considered a common examination for dentistry problems. Cellular biology can be affected by exposure to ionizing radiations procedures. In this study, we aimed to assess the genotoxicity and cytotoxicity effects of CBCT dental examinations at two different fields of view (FOVs) in exfoliated buccal epithelial cells. Methods: Sixty healthy adults participated in the current study. They were divided into two identical groups; CBCT with FOV of 6*6 cm2 and 8*11 cm2. Exfoliated oral mucosa cells were prepared immediately before and after 10-12 days of CBCT exposure. The cytological smears were stained with the Papanicolaou technique. The amounts of micronuclei and other cytotoxicity cellular changes (Pyknosis, Karyolysis, and Karyorrhexis) were evaluated. The variables of the parameters before and after CBCT examination in the two investigated FOVs were performed using Wilcoxon test and paired-samples t-test in SPSS software. Results: The micronuclei and other cytotoxic changes parameters before and after CBCT exposure for both FOVs (6*6 and 8*11 cm2) increased significantly (p<0.001). Furthermore, a significant difference (p<0.05) was observed between the investigated parameters at the two FOVs. Notably, the FOV of 8*11 cm2 had more side effects than that of 6*6 cm2. There were no statistically significant among males and females for both FOVs. Conclusion: CBCT examinations of dental disorders would increase the risks of inducing genetic damage. The cytotoxicity and chromosomal damage were considered in males and females in both investigated FOVs (6*6 and 8*11 cm2). In this regard, the use of CBCT must be following the ALARA principle.